Evaluación de los indicadores productivos y porcentaje de grasa corporal en pollo broilers alimentados con balanceado y semilla de linaza (Linum usitatissimum) en la provincia de Cotopaxi, cantón Salcedo, barrio el calvario - Pérez Navarrete, Johanna Roxana (2013)
This research was conducted Salcedo Canton, Neighrhood Calvario” and it was carried out during five days. The objective of the investigation was to assess the productive indicators in broiler chickens fed with elaborated food diet and treatment by a balanced product with seeds of linseed. Was performed eight bromatological analysis of the balanced diet to be applied on feeders. Selecting eighty broiler chickens unsexed and one day old. They were placed into 2 compartments, in groups of 40 mixed birds. The compartments were identified according to the level of diet, as follows: T0 food balanced, T1 balanced with seeds of linseed.